Development of nearpod-based e module on science material "energy and its changes" to improve elementary school student learning achievement - Alkhadad Feri; Zulherman Zulherman (International Journal of Education and Learning, 2021)
This study aims to (1) know the process of creating e-module-based learning media on energy materials and their changes in Nearpod applications for elementary students, (2) know the feasibility of energy learning e-module media products and their changes to the Nearpod application for elementary school students who are eligible for use in Natural Science learning. This study uses a Research and Development (RD) model. Based on preliminary studies, there is still a lack of interactive learning media based on technology to support and increase the enthusiasm of students' learning. A learning media is needed that can help teachers and students with learning activities. This research is based on previous preliminary studies that have been carried out, and the aim is to conduct a feasibility test of a research product developed. The development model used is the ADDIE model. The data collection techniques used are interview and questionnaire methods. Data analysis used descriptive percentage analysis. The results of the analysis showed media expert validation = 72.31% with Agree criteria, Material experts = 83.07% with Strongly Agree criteria, Feasibility test of teachers at SDN 1 Tukak Sadai and SDN 2 Tukak Sadai = 97.86% with the criteria of Strongly Agree and the product feasibility test on students = 95.28% with the criteria of Strongly Agree. This contributes to the Nearpod-Based Development of E-Modules to Improve the Learning Achievement of Elementary School Students.